Analisis Dampak Etika Kerja Dalam Mendukung Transformasional Organisasi Pada Satuan Polisi Pamong Praja Kota Gunungsitoli - Iman Selamat Gulo; Meiman Hidayat Waruwu; Ayler Beniah Ndraha; Odaligoziduhu Halawa (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to provide a partial analysis of the impact of work ethics in supporting organizational transformation and to determine the factors that hinder work ethics in supporting organizational transformation in the Gunungsitoli City Satpol PP. In conducting this research, the type of research used is a descriptive qualitative research method, the data collection techniques used in this research are observation, interviews and documentation. The researcher carried out direct observations in the field to find out the behavior and meaning of the behavior being studied and then the researcher conducted interviews to obtain as much data or information as possible and as clear as possible from the research subjects, namely key informants and supporting informants. The data analysis techniques used by researchers are data collection, data reduction, data presentation, and drawing conclusions. Based on the research results, it was concluded that the implementation of the responsibilities of the Gunungsitoli City Civil Service Police Unit members had been carried out quite well. However, there is still something that needs to be improved by several members of the Gunungsitoli City Satpol PP who still have not demonstrated a positive work ethic, namely work discipline and perseverance.